Мышечная система самки клеща Varroa jacobsoni (Parasitiformes, Varroidea) —паразита медоносной пчелы. II. Мышцы ходильных конечностей и идиосомы - Акимов, И.А.; Ястребцов, А.В. (Вестник зоологии, 1983)
Topography, morphology and possible functions of walking limbs and liosome muscles, articulation of leg joints are described in detail. Exopodal muscles are described first for gamasid mites. Peculierities in functioning of dorsoventral muscles, in particular participation of some of them in specific movements by means of a special “lock” type structure which provides fixation of coxa IV in immovable state are studied. A description and picture of the endosternite are presented; its role as an endoskeletal structure in the mite is shown. An analysis of the muscle topography and limb joint articulation revealed genu reduction in palps.